2021
DOI: 10.3390/ijms22126309
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Unique Combination of the Whole-Body Low Dose Radiotherapy with Inactivation of Two Immune Checkpoints and/or a Heat Shock Protein on the Transplantable Lung Cancer in Mice

Abstract: Non-small cell lung cancer (NSCLC) continues to be the leading cause of cancer death worldwide. Recently, targeting molecules whose functions are associated with tumorigenesis has become a game changing adjunct to standard anti-cancer therapy. As evidenced by the results of preclinical and clinical investigations, whole-body irradiations (WBI) with X-rays at less than 0.1–0.2 Gy per fraction can induce remissions of various neoplasms without inciting adverse side effects of conventional chemo- and radiotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…In all these cases, five consecutive irradiations of mice at 0.02 or 0.2 Gy of X-rays per day significantly suppressed the growth of murine tumour cells, either in the lungs (Figure 2) or under the skin (data not shown). 55 Similar results were also obtained in tumour-bearing rats. In a study conducted at the Hokkaido University School of Medicine in Sapporo, Japan, WKHA rats were subcutaneously implanted with allogeneic KDH-8 hepatoma cells (which metastasize to the lungs) and 14 days later irradiated at 0.2 Gy by X-rays; the radiation was delivered either to the whole body or only to the site of tumour implantation.…”
Section: Research and Data Invalidating The Lnt Paradigmsupporting
confidence: 69%
See 2 more Smart Citations
“…In all these cases, five consecutive irradiations of mice at 0.02 or 0.2 Gy of X-rays per day significantly suppressed the growth of murine tumour cells, either in the lungs (Figure 2) or under the skin (data not shown). 55 Similar results were also obtained in tumour-bearing rats. In a study conducted at the Hokkaido University School of Medicine in Sapporo, Japan, WKHA rats were subcutaneously implanted with allogeneic KDH-8 hepatoma cells (which metastasize to the lungs) and 14 days later irradiated at 0.2 Gy by X-rays; the radiation was delivered either to the whole body or only to the site of tumour implantation.…”
Section: Research and Data Invalidating The Lnt Paradigmsupporting
confidence: 69%
“…*indicates statistically significant (p > 0.05) difference against the result obtained in the control (0 Gy) group (modified, after Ref. 55). …”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…IRF7's impact on type I IFN regulation leads to immune microenvironment shifts, from immunosuppressive to anti-tumor dominance (38). However, IRF7's behavior is context-dependent, as it can exhibit both tumor-promoting and tumor-suppressing properties, depending on the speci c tumor-associated immune system (TAIS) dynamics (39)(40)(41)(42)(43)(44)(45).…”
Section: Discussionmentioning
confidence: 99%
“…Nowosielska et al. ( 196 ) found that LDRT to the whole-body (0.1 or 1.0 Gy) combined with anti-CTLA-4 antibody and anti-PD-1 antibody and NVP-AUY922 significantly reduced tumorigenesis in mice, and inhibited the clonogenic potential of Lewis lung cancer cells in vitro . By using targeted radionuclide therapy to semi-selectively deliver radiation to mouse tumors, Patel et al.…”
Section: Low-dose Radiotherapy Reverses Tumor-suppressing Immune Systemmentioning
confidence: 99%